2018
DOI: 10.1177/0023677218763686
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an oscillometric blood pressure monitor in anesthetized pigs

Abstract: The purpose of this study is to evaluate the accuracy of an oscillometric blood pressure monitor in anesthetized pigs. Invasive blood pressure (IBP) and noninvasive blood pressure (NIBP) measurements were taken using a DRE Waveline Pro multiparameter monitor at four different time points in 17 pigs undergoing injectable anesthesia. NIBP measurements were taken on both the thoracic and pelvic limbs. Bland Altman analysis was used to assess agreement between methods and a linear mixed-effects model was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Arterial cannulation allows invasive blood pressure measurement, which is considered the gold standard of blood pressure monitoring in pigs. 16,17 Oscillometry may have resulted in underestimation of the blood pressure, 17,18 but there is conflicting literature regarding the accuracy of NIBP monitoring in pigs. 16,19,20 Despite this, trend analysis is still possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial cannulation allows invasive blood pressure measurement, which is considered the gold standard of blood pressure monitoring in pigs. 16,17 Oscillometry may have resulted in underestimation of the blood pressure, 17,18 but there is conflicting literature regarding the accuracy of NIBP monitoring in pigs. 16,19,20 Despite this, trend analysis is still possible.…”
Section: Discussionmentioning
confidence: 99%
“…In the authors’ experience, arterial cannulation can be more challenging when the blood pressure is low and arterial pulsations are more difficult to palpate, as suspected in this case. Arterial cannulation allows invasive blood pressure measurement, which is considered the gold standard of blood pressure monitoring in pigs 16,17 . Oscillometry may have resulted in underestimation of the blood pressure, 17,18 but there is conflicting literature regarding the accuracy of NIBP monitoring in pigs 16,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Modelling some aspects of diagnosis and treatment of ACS using a porcine hind limb has proven especially useful given their similar anatomy, size better suited for human instrumentation, and similar blood pressure-a physiological parameter vital in compartment syndrome. 2,24,25 Xanthos et al 26 studied baseline hemodynamics such as blood pressure in swine and found relatively similar values to those of humans, which is important when assessing perfusion pressure. Delta P or perfusion pressure values of relevance to pig physiology have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%